Long-term safety and efficacy of breast biopsy markers in clinical practice. (2nd January 2021) - Smith, Sharon; Taylor, Clayton R.; Kanevsky, Estella; Povoski, Stephen P.; Hawley, Jeffrey R.
ABSTRACT: Objective : Percutaneous breast and axillary core biopsy followed by marker placement are integral parts of a breast imager's practice benefiting both patients and clinicians. Marker placement is the standard to facilitate future care. The purpose of this study is to characterize the safety and performance of MammoMARK, CorMARK, and HydroMARK biopsy markers by evaluating device-related adverse events, device deficiencies, and long-term safety. Methods : A retrospective review of three radiology practices identified patients who underwent image-guided breast or axillary biopsies followed by marker placement between 1 January 2012 and 1 January 2017. Medical records were reviewed with adverse events related to marker placement and use recorded. Results : 768 markers were placed with three (0.4%) events recorded. Two device deficiencies and one non-serious adverse event occurred in three patients. Device deficiency events involved user errors deploying the markers, one to inability to locate the marker on post-biopsy imaging, and the second to misplacement relative to biopsy target. One non-serious adverse event involved inability to locate/retain the marker in a surgically resected specimen. No serious adverse events were reported. Conclusion : Placement of breast biopsy markers is safe with minimal associated risks. Issues related to device malfunction, durability, reliability, safety, or performance were not reported.